2020
DOI: 10.1186/s12944-020-01231-9
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis and Evaluation of hepatoprotective effect of Maytenus royleanus leaves extract against anti-tuberculosis drug induced liver injury in mice

Abstract: Background: Myrin®-p Forte is an anti-tuberclosis agent that can cause hepatic injuries in clinical settings. Maytenus royleanus (Celastraceae) is a medicinal plant, possesses antioxidant and anticancer activities. The hepatoprotective effect of the methanol extract of Maytenus royleanus leaves (MEM) against Myrin®-p Forte induced hepatotoxicity in mice was investigated.Methods: Mice were randomly parted into six groups (n = 6). Fixed-dose combination of Myrin®-p Forte (13.5 mg/ kg Rifampicin, 6.75 mg/kg Isoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…It was suggested to inhibit lipid peroxidation and scavenge hydroxide and superoxide radicals, thus improving the antioxidant battery, the active constituents present in PAE such as flavonoids and vitamin C. In this context, the protective role of PAE may be due to the antiperoxidant and antioxidant effects of its components. These findings are in line with the latest reports (Al-Seeni et al, 2018& Elkomy et al, 2020 In addition, the current study pointed out that the administration of ATB resulted in a substantial increase in the serum level of inflammatory cytokines (TNF alpha & IL-1β) as well as the percentage of DNA fragmentation; this finding is agonised by recent data from Wali et al (2020) and Shabbir et al (2020). TNF alpha and IL-1β are active pro-inflammatory cytokines and are significant mediators of damage to inflammatory tissue.…”
Section: Discussionsupporting
confidence: 92%
“…It was suggested to inhibit lipid peroxidation and scavenge hydroxide and superoxide radicals, thus improving the antioxidant battery, the active constituents present in PAE such as flavonoids and vitamin C. In this context, the protective role of PAE may be due to the antiperoxidant and antioxidant effects of its components. These findings are in line with the latest reports (Al-Seeni et al, 2018& Elkomy et al, 2020 In addition, the current study pointed out that the administration of ATB resulted in a substantial increase in the serum level of inflammatory cytokines (TNF alpha & IL-1β) as well as the percentage of DNA fragmentation; this finding is agonised by recent data from Wali et al (2020) and Shabbir et al (2020). TNF alpha and IL-1β are active pro-inflammatory cytokines and are significant mediators of damage to inflammatory tissue.…”
Section: Discussionsupporting
confidence: 92%
“…In a metaanalysis, it was revealed that rifampicin increased the prevalence of drug-induced liver injury in a multidrug regimen from 1.6% to 2.55% in adults [14]. Hepatotoxicity attributed to anti-TB drugs has been reported 5-34.9% in people treated with anti-TB drugs [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The detoxification enzyme activities in P. xylostella samples treated with methoxyfenozide TC and Me@FL-SiO 2 NPs were observed in a Corning ® 96 Well Clear Polystyrene Microplate, after preparing the homogenates following the methodology [ 38 , 39 ]. About five third-instar of P. xylostella larval populations were crushed with mortar pestle and homogenized on ice in 1.5 mL of 0.1 M PBS (pH 7.8), comprising 1 mM phenyl thio urea (PTU), 1 mM phenylmethyl sulfonyl fluoride (PMSF), 1 mM dithiothreitol (DTT), and 1 mM ethylene diamide tetra acetic acid (EDTA).…”
Section: Methodsmentioning
confidence: 99%